Newborn outcomes in a cohort of premature babies born to HIV infected mothers: a single centre experience. (7th June 2011) - Sarwar, M I; Kingston, M; Edi-Osagie, N
Abstract : Background: Premature babies born to HIV positive mothers are at an increased risk of vertical transmission. This is complicated by the limited choice and the absence of adequate antiretroviral dosing and safety data. There is also an association between oral antiretrovirals and necrotising enterocolitis (NEC). The aim of this study is to review the experience of a neonatal unit in the management of premature babies born to HIV positive mothers. Methods: Retrospective single centre study looking at all premature babies born to HIV positive mothers from 2008 to 2010. Infant management, maternal antenatal therapy and babies' subsequent progress were analysed. Results: A total of 10 premature babies were born to HIV positive mothers from 2008 to 2010. 5 babies were <34 weeks gestation with birth weights ranging from 880 g to 1880 g (mean 1340 g). All these babies were managed with a combination of intravenous zidovudine and oral nevirapine and lamivudine. In our cohort, one baby developed fulminant NEC and died. Conclusions: Although the causal effect of oral antiretrovirals in the development of NEC is still not clear, our experience highlight the problem of using oral antiretrovirals in preterm babies. We suggest withholding the use of oral antiretrovirals in preterm babies most at risk of NEC. To further minimise risk, we suggest using donor milk when establishing feeds. Efforts at infant prophylaxis should also be concentrated on loading the infant via the mother before delivery.